RANCANG BANGUN SISTEM INFORMASI PENJUALAN APARTMENT JATINANGOR CITY PARK - Erna Hikmawati (NUANSA INFORMATIKA, 2019)
PT. Koryza (KurniaOryzaAbadi) is a company engaged in property in Cibeusi, Jatinangor, Sumedang Regency, West-Java. On the running system, PT. KoryzaAbadi is still using a ledger; Microsoft word and Microsoft excel in the transaction management. It is very ineffective and efficient when sales admin searches customer’s data that do a unit transaction, installment per month transaction, and a unit data, which are still available. Based on the problem,  it is built an  information that is expected to facilitate sales admin in collecting the data and recording sales transaction that can be more effective and efficient. The approach method used in developing this information system is object-oriented method, whereas programming language used is PHP with MySQL as its database. The information system built can manage the data of prospective buyers, buyer data and unit data, and it can provide notification to the buyer's due to date of buyer's repayment, the racketeering to the marketing staff based on many units sold and it can display sales chart, turnover that can be obtained and number of units that are sold and available. Keywords: Information System, Sales, Apartment, PHP, MySQL